2008
DOI: 10.1111/j.1439-0485.2008.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioconstructional features of the coral Cladocora caespitosa (Anthozoa, Scleractinia) in the Adriatic Sea (Croatia)

Abstract: The Mediterranean endemic Cladocora caespitosa (Linnaeus, 1767) is a colonial scleractinian coral belonging to the family Faviidae and the only zooxanthellate coral from Mediterranean whose colonies may fuse in reef‐like structures (hermatypic). Recent surveys are focused on three locations where banks occur in the Adriatic Sea (Croatia): near Prvić Island in the northern Adriatic, near Pag Island in the central Adriatic and in Veliko jezero (Mljet National Park) in the southern Adriatic. The C. caespitosa ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 37 publications
2
52
1
Order By: Relevance
“…The fossil Santa Teresiola coral bank probably developed under similar SST regimes which are comparable to those recorded today in the coldest regions of Eastern Adriatic Sea, where cold winds or inputs of freshwater may lower the SST temperature on the coral banks (BenoviT et al 2000;Novosel et al 2004;Montagna et al 2007;KruqiT and BenkoviT 2008). Mastronuzzi et al (2003) and Mastronuzzi (2006) concluded that the fossil C. caespitosa bank of Santa Teresiola existed in a lagoon aVected by inputs of freshwater.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The fossil Santa Teresiola coral bank probably developed under similar SST regimes which are comparable to those recorded today in the coldest regions of Eastern Adriatic Sea, where cold winds or inputs of freshwater may lower the SST temperature on the coral banks (BenoviT et al 2000;Novosel et al 2004;Montagna et al 2007;KruqiT and BenkoviT 2008). Mastronuzzi et al (2003) and Mastronuzzi (2006) concluded that the fossil C. caespitosa bank of Santa Teresiola existed in a lagoon aVected by inputs of freshwater.…”
Section: Discussionmentioning
confidence: 85%
“…In this lagoon, SST vary between 9 and 29°C and salinity shifts from 36.3 to 39 PSU (Vanibek et al 2000;KruqiT and Poqar-Domac 2003). Although the Santa Teresiola reef refers to a warm climatic phase of the Pleistocene, the diVerences between the temperature of the lagoon and the warmer open-sea temperatures of MISs 5.5 could be explained by freshwater coming from underwater, karstic springs that are common today both in Croatia and in the Taranto area (Pagliarulo and Bruno 1990;KruqiT and BenkoviT 2008). These assumptions also agree with palaeontological records of other fossil reefs found in alluvial deposits dating back as far as to the Late Pliocene (Aguirre and Jiménez 1998;Fornos et al 1996) where 'beds' of the bivalve Ostrea spp., a suspension feeder characteristic of environments with cold seawater, lower salinity and high turbidity, forms the basement or is intercalated in coral banks (Bernasconi et al 1997;Aguirre and Jiménez 1998;Dornbos and Wilson 1999).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations